The Characteristics and Features of Epigraphic Inscriptions of Waqfs in Algeria. A Study of a Sample - BENDJEDOU, Abdelfatah (Jordan Journal for History and Archaeology, 2025)
This research paper studies a set of epigraphic inscriptions of Waqfs in Algeria. The aim is to extract the most important aspects and characteristics of these epigraphic inscriptions, including their formal and artistic aspect, such as the materials on which they was written, types of fonts and methods of implementation. The study also focuses on the content of these inscriptions, examining aspects like language, terminology and other valuable data they provide to historians and archaeologists, such as place names, religious establishments, some economic activities and types of coins and their values. These aims are achieved by reviewing a sample of nine inscriptions, categorized as movable and immovable monuments. Some of these inscriptions are still in their original places, while others are part of museum collections. Their dates range from the end of the seventh century to the beginning of the thirteenth century AH.